Terpenoids from the barks of Magnolia maudiae (Dunn) Figlar. Issue 13 (3rd July 2018) - Xianjin, Sui; Sha, Shi; Qi, Muge; Zhang, Zhengxi; Yang, Yuyao; Wu, Haibo; Li, Linfeng; Wang, Wenshu; Huang, Anmin
Abstract: A new germacrenolide (1 ) and fourteen known terpenoids (2–15 ) were isolated from the barks of Magnolia maudiae (Dunn) Figlar (Magnoliaceae). The structure of (7 α H, 11 β H)-2 α, 8 α -dihydroxy-4 α, 5 β -epoxy-germacr-1(10)-en-6 α, 12-olide (1 ) was elucidated by physical and spectroscopic data analysis, including 1D, 2D NMR and HR-ESI-MS. Lyratol F (9 ) was isolated from Magnolia for the first time. The structures of known compounds were established by comparing their spectroscopic data with those in literatures. Abstract :